2022
DOI: 10.1039/d2qo00412g
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-mediated defluorinative cyclization of α-fluoro-β-enamino esters catalyzed by 4-CzIPN

Abstract: Using 4-CzIPN as an energy transfer (EnT) photocatalyst and α-fluoro-β-enamino esters as the substrates, a mild 6π-photocyclization/defluorination of N-aryl enamines was carried out to efficiently construct indoles without oxidant and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…To verify our hypothesis, we explored cyclopropanation using N -tosylhydrazone 1a and 1,1-diphenylethylene 1b as model substrates. To our delight, the corresponding cyclopropane bearing two quaternary centers was successfully synthesized in our initial attempts using different photosensitizers, which showed that 2,4,5,6-tetra­(carbazol-9-yl)­benzene-1,3-dicarbonitrile (4-CzIPN), with a triplet energy of 60.0 kcal/mol, is the most suitable photosensitizer (Table , entries 1–6). Other photosensitizers, including Eosin Y (43.5 kcal/mol), Ir­[(dtbbpy)­(ppy) 2 ]­PF 6 (49.2 kcal/mol), fac -Ir­(ppy) 3 (57.8 kcal/mol), and Ir­( p -F-ppy) 3 (58.6 kcal/mol), exhibited lower reactivity, presumably because they possess lower triplet energy than that of 4-CzIPN.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…To verify our hypothesis, we explored cyclopropanation using N -tosylhydrazone 1a and 1,1-diphenylethylene 1b as model substrates. To our delight, the corresponding cyclopropane bearing two quaternary centers was successfully synthesized in our initial attempts using different photosensitizers, which showed that 2,4,5,6-tetra­(carbazol-9-yl)­benzene-1,3-dicarbonitrile (4-CzIPN), with a triplet energy of 60.0 kcal/mol, is the most suitable photosensitizer (Table , entries 1–6). Other photosensitizers, including Eosin Y (43.5 kcal/mol), Ir­[(dtbbpy)­(ppy) 2 ]­PF 6 (49.2 kcal/mol), fac -Ir­(ppy) 3 (57.8 kcal/mol), and Ir­( p -F-ppy) 3 (58.6 kcal/mol), exhibited lower reactivity, presumably because they possess lower triplet energy than that of 4-CzIPN.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…[37] The observed photoinduced E!Z isomerization of cinnamyl systems is a well-known process. [38][39][40][41][42][43][44] For example, Stephenson and co-workers [39] exposed (E)-2iodo-cinnamyl alcohol to standard reaction conditions with Ir(ppy) 3 and observed efficient dehalogenation, although the reduced allylic alcohol consisted of a mixture of E:Z isomers with a photostationary compo- sition (Z:E) of 3.5:1. They verified the existence of an energy transfer pathway by exposing trans-cinnamyl alcohol to the Ir photocatalyst, which yielded comparable results.…”
Section: Resultsmentioning
confidence: 99%
“…The observed photoinduced E→Z isomerization of cinnamyl systems is a well‐known process [38–44] . For example, Stephenson and co‐workers [39] exposed ( E )‐2‐iodo‐cinnamyl alcohol to standard reaction conditions with Ir(ppy) 3 and observed efficient dehalogenation, although the reduced allylic alcohol consisted of a mixture of E : Z isomers with a photostationary composition ( Z : E ) of 3.5:1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations